The Contribution of Anterior Segment Abnormalities to Changes in Intraocular Pressure in the DBA/2J Mouse Model of Glaucoma: DBA/2J-Gpnmb+/SjJ Mice as Critical Controls - Rohowetz, Landon J.; Mardelli, Marc E.; Duncan, R. Scott; Riordan, Sean M.; Koulen, Peter (Frontiers in Neuroscience, 2022)
The contributions of anterior segment abnormalities to the development of ocular hypertension was determined in the DBA/2J mouse model of glaucoma. Intraocular pressure (IOP) was measured noninvasively. Iris pigment dispersion (IPD) and corneal calcification were measured weekly starting at 20 weeks of age in DBA/2J and DBA/2J-Gpnmb+/SjJ mice. Thickness, surface area, auto-fluorescence intensity, and perimeter length of calcified regions were measured in postmortem corneas using confocal microscopy. DBA/2J mice developed elevated IOP between 9 and 12 months of age, but DBA/2J-Gpnmb+/SjJ mice did not. Corneal calcification was found at all ages observed and at similar frequencies in both strains with 83.3% of DBA/2J eyes and 60.0% of DBA/2J-Gpnmb+/SjJ eyes affected at 12 months (P = 0.11). Calcification increased with age in both DBA/2J (P = 0.049) and DBA/2J-Gpnmb+/SjJ mice (P = 0.04) when assessed qualitatively and based on mixed-effects analysis. No differences in the four objective measures of calcification were observed between strains or ages. At 12 months of age, DBA/2J mice with corneal calcification had greater mean IOP than DBA/2J mice without corneal calcification. IOP was not correlated with the qualitatively assessed measures of calcification. For the subset of eyes with ocular hypertension, which were only found in DBA/2J mice, IOP was negatively correlated with the qualitative degree of calcification, but was not correlated with the four quantitative measures of calcification. Differences in IOP were not observed between DBA/2J-Gpnmb+/SjJ mice with and without calcification at any age. IPD increased with age and demonstrated a moderate correlation with IOP in DBA/2J mice, but was not observed in DBA/2J-Gpnmb+/SjJ mice. In the DBA/2J mouse model of glaucoma, increased IPD is positively correlated with an increase in IOP and corneal calcification is present in the majority of eyes at and after age 9 months. However, while IPD causes ocular hypertension, corneal calcification does not appear to contribute to the elevation of IOP, as the control strain DBA/2J-Gpnmb+/SjJ exhibits corneal calcification similar to DBA/2J mice, but does not develop ocular hypertension. Corneal calcification, therefore, does not appear to be a contributing factor to the development of elevated IOP in DBA/2J mice.